Monitoramento de temperatura e umidade de ambientes indoor com uso de sensores IoT e realidade aumentada - Matsuo, Ângela Kimie (Brasil, 2024)
This work explores the growing application of the Internet of Things (IoT) in building installations and in the management of contexts such as temperature and humidity, highlighting the need to present IoT sensor data in a way that is accessible to building supervisors and other nontechnical audiences. It is proposed to develop a layer for handling and visualising thermal sensor data in indoor environments, using augmented reality and integrating data into a 3D virtual reality environment. This approach aims not only to provide an intuitive visual representation, but also to guarantee a practical understanding of thermal comfort conditions. The results indicate that the system developed enables effective real-time monitoring of environmental conditions, providing users with a valuable tool for optimising thermal comfort in indoor facilities, especially for building supervisors. This study contributes to the use of innovative technologies, demonstrating how the strategic integration of IoT, BIM (Building Information Modelling) and virtual reality can meet the practical demands of building management, making information accessible and understandable to diverse audiences